Rapid Identification of Commercial Frankincense Products by MALDITOF Mass Spectrometry - Lai, Shang-Chih; You, Ren-In; Chen, Tz-Ting; Chang, Yu; Liu, Chao-Zong; Chen, Hao-Ping; Wu, Chunhung (Combinatorial Chemistry & High Throughput Screening, 2022)
Background: Frankincense is a resin secreted by the Boswellia tree. It is used in perfumery, aromatherapy, skincare, and traditional Chinese medicine. However, all Boswellia species are under threat owing to habitat loss and overexploitation. As a result, the market is getting flooded with counterfeit frankincense products. Objective: This study aims to establish a high-throughput method to screen and identify the authenticity of commercial frankincense products. We report, for the first time, a matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS)-based method for rapid and high-throughput screening of frankincense samples. Methods: MALDI-TOF MS, HPLC, thin-layer chromatography (TLC), and in vitro antiinflammatory activity assay were used to examine the frankincense samples. Results: Well-resolved peaks of frankincense triterpenoids in the spectra were observed in the crude extract of commercial samples, including α-boswellic acids (αBAs), β-boswellic acids (βBAs), 11-keto-β-boswellic acids (KBAs), acetyl-11-keto-β-boswellic acids (AKBAs), and their esters. These compounds can be used as indicators for determining the authenticity of frankincense. Conclusion: Unlike LC–MS, which is a time-consuming and expensive method, and TLC, which requires a reference sample, our inexpensive, rapid high-throughput identification method based on MALDI-TOF MS is ideal for large-scale screening of frankincense samples sold in the market.
Keywords: Acetyl-11-keto-β-boswellic acid